2020
DOI: 10.1080/10911359.2020.1854141
|View full text |Cite
|
Sign up to set email alerts
|

Does social support affect perceived stress? A research during the COVID-19 pandemic in Turkey

Abstract: This study aims to examine the effects of multidimensional social support perceptions on the stress levels of people aged 18 and over. The universe of the study consists of individuals aged 18 and over living in Turkey; 802 people participated in the study where the convenience sampling method was used. The data were collected through a questionnaire created on the internet via Google Form. Descriptive statistical methods, reliability analysis, correlation analysis, and multiple regression analysis were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
2
10
0
3
Order By: Relevance
“…Potentially, sense of connectedness to close groups encompasses aspects that are more important with respect to the pandemic's implications for well‐being (such as support with the challenges of everyday life) than more distant groups. This finding is compatible with previous research revealing the importance of connectedness to family members (Li & Xu, 2020 ), friends (Özer et al, 2021 ), and neighbours (Sibley et al, 2020 ) for well‐being during the COVID‐19 contact restrictions. However, it goes beyond these results by demonstrating that feeling connected to these groups predicts well‐being even when controlling for connectedness to other groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Potentially, sense of connectedness to close groups encompasses aspects that are more important with respect to the pandemic's implications for well‐being (such as support with the challenges of everyday life) than more distant groups. This finding is compatible with previous research revealing the importance of connectedness to family members (Li & Xu, 2020 ), friends (Özer et al, 2021 ), and neighbours (Sibley et al, 2020 ) for well‐being during the COVID‐19 contact restrictions. However, it goes beyond these results by demonstrating that feeling connected to these groups predicts well‐being even when controlling for connectedness to other groups.…”
Section: Discussionsupporting
confidence: 92%
“…During the COVID‐19 contact restrictions, these factors may have been particularly relevant as individuals may have experienced worries due to the pandemic and impaired work‐life balance due to limited childcare. In support of this claim, feeling connected to one's neighbours during the COVID‐19 lockdown in New Zealand was positively associated with psychological well‐being (Sibley et al, 2020 ), perceived support from family members was positively associated with mental health during the COVID‐19 contact restrictions in China (Li & Xu, 2020 ), and perceived social support from family members and friends was associated with reduced stress during the pandemic in Turkey (Özer, Özkan, Budak, & Özmen, 2021 ).…”
Section: Sense Of Connectedness During the Covid‐19 Contact Restrictionsmentioning
confidence: 99%
“…As, human behavior has a strong impact on controlling the spread of COVID-19 pandemic, understanding the psychological responses in COVID-19 pandemic including anxiety and stress could inform intervention policies and the programs to combat COVID-19 by the public health officials and policy makers [ 3 ]. A study showed that college students are challenged during COVID-19 pandemic by psychological, social, and academic problems [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 caused pneumonia is now a global disease that is highly infectious and threatens public health [ 1 , 2 ]. COVID-19 pandemics, affecting all the world, affect people not only physically but also psycho-social [ 3 ]. Expansion of epidemics intensifies or creates new stressors such as stress, fear and worry of oneself and loved ones’ health [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cognitive empathy has been associated with a decrease in intergroup conflict and prejudice, and affective empathy has been shown to promote altruism and caring [3,16,17]. Currently, studies have demonstrated that social support has been one of the important predictors of resilience during a global pandemic [1,18]; however, the links between social support and empathy remain unclear.…”
Section: Introductionmentioning
confidence: 99%